Discourse in curriculum: A focus on film, television, and media studies - Firdaus Noor; Nuril Ashivah Misbah; Dede Suprayitno; Putrawan Yuliandri (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
This article using discourse theory, popularized by Foucault, is used to examine the production and use of knowledge and practices relevant to the discourse that applies to the film, television, and media studies study program curriculum. This research uses the interpretive phenomenology method (Interpretative Phenomenological Analysis), and the classification and framing of data are carried out through focused group discussions. The purposeful sampling technique was chosen through a maximum variation sampling strategy involving eight research subjects to understand the various experiences of campuses that already have similar programs and are considered the most